The Influence of Religiosity, Waqf Literacy and Trust on the Intention to Pay Cash Waqf: A Case Study - Fathurrohman Ramadan; Izra Berakon (International Journal of Waqf, 2025)
This study aims to examine the influence of religiosity, waqf literacy, and trust on the intention to pay cash waqf with a case study of UIN Sunan Kalijaga Yogyakarta Students. This study is a quantitative research with a data collection method using questionnaires. Of the 136 data collected, it was processed using the Partial Least Square – Structure Equation Modelling (PLS-SEM) approach with the help of SmartPLS 3.0. The results of the study show that the variables of religiosity, waqf literacy, and trust have a significant positive effect on a person's attitude in the intention of paying cash waqf. Subjective norms and perceptions of behavior control also have a significant positive effect on the intention to pay cash waqf.